Efficacy and Safety of Direct-Acting Oral Anticoagulants Use in Acute Portal Vein Thrombosis Unrelated to Cirrhosis - Nery, F. (2017)
Submitted by José Pereira (jro.pereira@gmail.com) on 2017-09-07T08:45:32Z No. of bitstreams: 1 Efficacy and Safety of Direct-Acting Oral Anticoagulants.pdf: 835166 bytes, checksum: b77d70982419d9a41e022505892056eb (MD5)